Molecular Analysis of the E2F/DP Gene Family of Daucus carota and Involvement of the DcE2F1 Factor in Cell Proliferation - Perrotta, Lara; Giordo, Roberta; Francis, Dennis; Rogers, Hilary J.; Albani, Diego (Frontiers in Plant Science, 2021)
E2F transcription factors are key components of the RB/E2F pathway that, through the action of cyclin-dependent kinases, regulates cell cycle progression in both plants and animals. Moreover, plant and animal E2Fs have also been shown to regulate other cellular functions in addition to cell proliferation. Based on structural and functional features, they can be divided into different classes that have been shown to act as activators or repressors of E2F-dependent genes. Among the first plant E2F factors to be reported, we previously described DcE2F1, an activating E2F which is expressed in cycling carrot (Daucus carota) cells. In this study we describe the identification of the additional members of the E2F/DP family of Daucus carota, which includes four typical E2Fs, three atypical E2F/DEL genes and three related DP genes. Expression analyses of the carrot E2F and DP genes reveal distinctive patterns and suggest that the functions of some of them are not necessarily linked to cell proliferation. DcE2F1 was previously shown to transactivate an E2F-responsive promoter in transient assays but the functional role of this protein in planta was not defined. Sequence comparisons indicate that DcE2F1 could be an orthologue of the AtE2FA factor of Arabidopsis thaliana. Moreover, ectopic expression of the DcE2F1 cDNA in transgenic Arabidopsis plants is able to upregulate AtE2FB and promotes cell proliferation, giving rise to polycotyly with low frequency, effects that are highly similar to those observed when over-expressing AtE2FA. These results indicate that DcE2F1 is involved in the control of cell proliferation and plays important roles in the regulation of embryo and plant development.